Pengaruh Pupuk Kotoran Kambing dan Media Arang Sekam Terhadap Pertumbuhan Sawi Hijau (Brassica juncea L.) - Darso Septian; Rusmana Rusmana; Julio Eiffelt Rossaffielt Rumbiak; Dewi Firnia (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
One of the vegetable commodities with the highest economic worth is green mustard greens. Optimizing the usage of fertilizers and planting material can increase the yield of green mustard greens. Plant growth and soil quality may be sustainably enhanced by using rice husk charcoal and goat manure. Goat dung and rice husk charcoal are being used in this study to boost the development and production of green mustard greens until the ideal fertilizer dose and planting media ratio are determined. ln May and June of 2024, this survey was conducted on land owned by residents of Wanasari Villager, Cibeber Region, Lebak Regencies, Banten Province. ln this investigation, three replications and two variables were employed in a factorial randomized block design (RAK). Goat dung dosage is the first factor, and it comes in three levels: 0 g/polybag, 1000 g/polybag, and 2000 g/polybag. A comparison of three levels of rice husk charcoal 0 g rice husk charcoal media and 2000 g soil (0:2)/polybag, 1000 g rice husk charcoal media and 1000 g soil (1:1)/polybag, and 2000 g rice husk charcoal media and 1000 g soil (2:1)/polybag is the second factor. This process is repeated three times to yield 27 plants. ANOVA and a post hoc test employing the Duncan Multiple Range Test (DMRT) at the 5% level were employed in this investigation. Plant height, leaf quantity, main leaf length, main leaf breadth, fresh plant weight, root length, and wet root weight were the characteristics measured in this investigation. The goat manure dosage had a notably distinct impact on green mustard development across all criteria, with 1000 g/polybag being the optimal amount.